2017
DOI: 10.1002/2211-5463.12237
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses gastric cancer by inhibiting gastrin‐mediated acid secretion

Abstract: Hyperacidity in the stomach is known to promote the progression of gastric cancer. The plant‐derived chemotherapeutic curcumin is used to treat gastric cancer. The objective of this study was to investigate whether curcumin regulates gastrin‐mediated acid secretion in suppressing gastric cancer. Gastric cancer cells were treated with 25 μ m curcumin, followed by Annexin V/propidium iodide double‐staining assay to evaluate cell apoptosis. Western blot analysis was used to analyze caspase‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
0
17
0
2
Order By: Relevance
“…Curcumin has been considered as a promising approach for the treatment of multiple cancers, including gastric cancer, bladder cancer, renal cancer, etc [ 6 , 10 – 13 ]. Recently, several researchers also focused on the potential role of curcumin in Rb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin has been considered as a promising approach for the treatment of multiple cancers, including gastric cancer, bladder cancer, renal cancer, etc [ 6 , 10 – 13 ]. Recently, several researchers also focused on the potential role of curcumin in Rb.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, multiple therapeutic properties of curcumin have been recognized, including anti-inflammatory, anti-neoplastic [ 6 ], anti-oxidant [ 7 ], anti-fibrotic [ 8 ], and anti-ischemic [ 9 ] effects. Specifically regarding the anti-neoplastic function, curcumin has been reported to suppress the secretion of gastrin-mediated acid, and thereby inhibiting the progression of gastric cancer [ 10 ]. In vitro investigation has showed that curcumin inhibited bladder cancer cells growth and metastasis via regulating β-catenin expression [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well-documented that disproportionate stress [31,32] or gastrin upregulation [33] underlies the formation of stomach ulcers and excessive secretion of acids is conductive to the development of gastric cancer [34]. Opposing those effects, mucus and bicarbonate secretion form the first line of defense in protecting gastric epithelial cells from acids and digestive enzymes [1,11].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the reduction of cell viability, treatment with CH-5 increased apoptosis in a dose-dependent manner. We have found in other cell lines that CH-5 is capable of inducing 3/7 caspase activity and then promoting the cleavage of PARP [ 17 , 18 ], and curcumin has already been shown to induce caspases-mediated apoptosis in gastric cancer [ 23 , 24 ]. Thus, CH-5 is likely to trigger apoptosis in gastric cancer cells by the induction of caspases.…”
Section: Discussionmentioning
confidence: 99%